Anterior Cervical Discectomy With Fusion and Plating for Correction of Degenerative Cervical Kyphosis: 2-Dimensional Operative Video. Issue 3 (29th December 2020) - Guinn, Jeremy M V; Pennicooke, Brenton; Rivera, Joshua; Mummaneni, Praveen V; Chou, Dean
Abstract: This surgical video demonstrates the technique for correcting degenerative cervical kyphosis using an anterior cervical discectomy and fusion (ACDF). Degenerative cervical kyphosis can cause radiculopathy, myelopathy, and difficulty holding up one's head. The goal of surgical intervention is to alleviate pain, improve the ability for upright gaze, and decompress the spinal cord or nerve roots. Posterior-only approaches and anterior corpectomies are alternative treatments to address cervical kyphosis. However, an ACDF allows for sequential induction of lordosis via distraction over multiple segments and for further lordosis induction by sequential screw tightening, pulling the spine towards a lordotic cervical plate. 1 This video shows 2 cases demonstrating a technique of correcting severe cervical degenerative kyphosis. The video illustrates our initial kyphotic Caspar pin placement coupled with sequential anterior distraction to correct kyphosis. The technique is most useful in patients who have good bone density, nonankylosed facets, and degenerative cervical kyphosis. We have received informed consent of this patient to submit this video.